Prescribed use of methylphenidate hydrochloride and its correlates among Brazilian college students (Archives of Clinical Psychiatry, 2012)
BACKGROUND: The prevalence of prescribed use of methylphenidate (MPH) and its correlates are not well-known in Brazil. OBJECTIVE: To estimate the prevalence of prescribed use of MPH and its correlates in a sample of Brazilian college students. METHODS: Twelve-thousand seven hundred and eleven college students filled out a drug use questionnaire. They were divided into two groups based on the lifetime use of MPH: MPH users (MPHU) and MPH non-users (MPHNU). Quasi-binomial regression models were carried out in order to evaluate the correlation among MPHU and other variables. RESULTS: A lifetime use of MPH was reported from 0.9% of college students (MPHU). Being from the Midwest (PR = 4.8, p < 0.01) and South (PR = 5.2, p < 0.05), living in students housing (PR = 5.8, p < 0.001), prescribed use of amphetamines (PR = 8.9, p < 0.001) and benzodiazepines (< 3 weeks: PR = 4.4, p < 0.001; ≥ 3 weeks: PR = 6.7, p < 0.001), and harmful use of alcohol (PR = 4.0, p < 0.05) were correlated with MPHU. DISCUSSION: The association of alcohol and drug use with prescribed use of MPH among college students suggests the importance of screening drinking patterns and use of other drugs among students with ADHD symptoms.